Development of an integrated statistics pocket book on culture and Islamic value - Andi Asma; Kadir Kadir; Arhanuddin Arhanuddin; Muhammad Tahir (JINoP (Jurnal Inovasi Pembelajaran), 2024)
This research discusses the development of a statistical pocketbook integrated with Islamic values and culture to enhance students' understanding and appreciation of statistics within a cultural and religious context. This research aims to develop a statistical pocket book that meets valid criteria. This research uses the Research and Development (R&D) method. The development model used is ADDIE which consists of 5 development stages, namely: (1) analysis stage, (2) design stage, (3) development stage, (4) implementation stage, (5) evaluation stage. However, this development research only uses four stages, namely (1) analysis, (2) design, (3) development and evaluation. This research was conducted at FTIK IAIN Manado. Data collection was carried out using questionnaires and tests. Instruments were a marketing/content expert validation sheet and a media/design expert questionnaire validation sheet. Based on the results of the questionnaire analysis, the results obtained were that the statistics pocket book integrated with Islamic values and culture met the valid criteria for use in statistics learning, seen from the assessment results for validation by content/material experts (85%) with very valid categories and media/design experts (91 %) is also in the very valid category, the average percentage of the practicality test is 91% in the very practical category. So, the Statistics pocketbook that has been developed is valid and practical for use in learning because it is integrated with Islamic values and culture.